Collected writings of John Maynard Keynes Vol III Revision of the treaty being a sequel to the economic consequences of the peace - Johnson, Elizabeth (Ed.); Keynes, John Maynard (Cambridge Cambridge University Press, 2013)
From the ratification of the treaty of versailles to the second ultimatum of London